Acetaminophen (Paracetamol) Facilitated Extinction Lear ning in Contextual Fear Conditioned Rats - Zaman, Neelam; Ahmad, Hammad; Ali Abid, Mobasher; Nisar-ur-Rahman; Roome, Talat; Abbas, Ghulam (Letters in Drug Design & Discovery, 2017)
Background: The endogenous cannabinoid system (eCB) has been shown to play an important role in the extinction of aversive memories. AM404, the metabolite of paracetamol, was shown to enhance eCB signaling. Objective: The present study was designed to pre-clinically evaluate the effectiveness of paracetamol against Post-traumatic stress disorder (PTSD). Methods: Contextual Fear conditioning (CFC) was used as animal model of PTSD. The behavioral and biochemical indicators of anxiety were also measured using elevated plus maze (EPM) and corticosterone levels, respectively. Results: Our data showed that the paracetamol treatment (100, 250 and 500 mg/kg) caused significant dose dependent decrease in animal’s freezing behavior in fear conditioned rats. The EPM data revealed that the treated rats spent more time in the open arm of elevated plus maze. However, the corticosterone levels remained unaltered. Conclusion: The present study provide robust evidence that the paracetamol, having established safety in humans, holds promise against PTSD and merits further investigation as potential lead compound in anti-PTSD drug development program.
Keywords: post-traumatic stress disorder